Estudar e trabalhar: experiências laborais de jovens estudantes durante o (novo) Ensino Médio - Ribeiro, Vinicius Leonardo (Universidade Federal de São Carlos, 2025)
Based on the set of educational and labor reforms implemented in Brazil since 2017, this research aims to understand the school and work experiences of high school students and the possible changes in the relationships they establish with school and work in the context of the so-called “new High School.” It also seeks to highlight their perspectives for the future regarding the continuation of their studies or (re)entry into the workforce. This qualitative research was conducted with students from two public schools participating in the Full-Time Education Program in the municipality of Sorocaba. The methods used included a literature review, the formation of seven discussion groups involving 40 young people, and seven in-depth interviews with students who had participated in the discussion groups. The participants expressed the difficulties brought about by changes in the educational curricula, a lack of interest in taking the National High School Exam—since they do not feel prepared—and a significant disconnect between the educational pathways offered and their own future perspectives, whether in relation to work or to the continuation of their studies. The results also show that the young people had a significant presence in the workforce, mainly in informal positions, and that even in contracts labeled as “internships”, what can be observed is a form of rights deprivation in their first jobs, as well as the absence of apprenticeship contracts, either due to the limited reach of this policy or because of difficulties in accessing such opportunities as a result of changes to school schedules.
Studying and working: labor experiences of young students during the (new) High School
Keywords: Educação; Juventude; Trabalho; Ensino Médio; Escolas de Tempo Integral; Sorocaba; Education; Youth; High School; Full-Time Schools; CIENCIAS HUMANAS